Utopian Pragmatism: Scotland's Choice. Issue 1 (February 2015) - Paterson, Lindsay
<x xml:space="preserve">Abstract</x> The Scottish referendum of autumn 2014 has been debated as if it was a unique moment in the country's history, and in several senses it was indeed unprecedented – in the level of engagement by citizens which it stimulated, in the acceptance by all sides to the debate that the decision on independence was Scotland's alone (which was an implicit recognition of popular sovereignty), and in its being the first ever democratic and explicit endorsement of the Union by Scotland. Nevertheless, there is also a sense in which the pattern of protest and compromise that led to the referendum and that pervades its aftermath is very familiar – the latest in a series of such processes that have characterised Scotland's always evolving place in the Union since 1707. Radical challenge is followed by pragmatic adjustment as the state cedes just enough power to keep the Union intact for the time being, a compromise which sows the seeds of the next phase of radical rebellion. That is why Scotland's position never fully satisfies anyone, and why, on this occasion, the basis for a new challenge to the Union (and for a new compromise to that new challenge) has probably already been laid before even the outcome of this referendum has been fully settled.